β-glucans: a potential source for maintaining gut microbiota and the immune system - Singh, Ravindra Pal; Bhardwaj, Aditi (Frontiers in Nutrition, 2023)
The human gastrointestinal (GI) tract holds a complex and dynamic population of microbial communities, which exerts a marked influence on the host physiology during homeostasis and disease conditions. Diet is considered one of the main factors in structuring the gut microbiota across a lifespan. Intestinal microbial communities play a vital role in sustaining immune and metabolic homeostasis as well as protecting against pathogens. The negatively altered gut bacterial composition has been related to many inflammatory diseases and infections. β-glucans are a heterogeneous assemblage of glucose polymers with a typical structure comprising a leading chain of β-(1,4) and/or β-(1,3)-glucopyranosyl units with various branches and lengths as side chain. β-glucans bind to specific receptors on immune cells and initiate immune responses. However, β-glucans from different sources differ in their structures, conformation, physical properties, and binding affinity to receptors. How these properties modulate biological functions in terms of molecular mechanisms is not known in many examples. This review provides a critical understanding between structures of β-glucans and their functions for modulating the gut microbiota and immune system.